2022
DOI: 10.3390/metabo12030268
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid as a Potential Prostate Cancer Biomarker Determined in Various Biological Samples

Abstract: Despite numerous studies, the molecular mechanism of prostate cancer development is still unknown. Recent investigations indicated that citric acid and lipids—with a special emphasis on fatty acids, steroids and hormones (ex. prolactin)—play a significant role in prostate cancer development and progression. However, citric acid is assumed to be a potential biomarker of prostate cancer, due to which, the diagnosis at an early stage of the disease could be possible. For this reason, the main goal of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We hypothesize that PC cells take up this serum citrate through specific transporters expressed in the plasma membrane [ 34 , 35 ], and intracellularly utilize it to support PC metabolism, proliferation, fatty acid synthesis, and protein acetylation [ 36 ]. Similar findings were reported by Buszewska-Forajta et al (2022), who observed higher serum concentrations of citrate in a PC group compared to a BPH group, with no significant changes in citrate concentration based on the clinical stage of the tumor [ 37 ]. In contrast, Kumar et al (2016) reported a significant decrease in citrate levels in filtered serum obtained from PC patients compared to BPH patients [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…We hypothesize that PC cells take up this serum citrate through specific transporters expressed in the plasma membrane [ 34 , 35 ], and intracellularly utilize it to support PC metabolism, proliferation, fatty acid synthesis, and protein acetylation [ 36 ]. Similar findings were reported by Buszewska-Forajta et al (2022), who observed higher serum concentrations of citrate in a PC group compared to a BPH group, with no significant changes in citrate concentration based on the clinical stage of the tumor [ 37 ]. In contrast, Kumar et al (2016) reported a significant decrease in citrate levels in filtered serum obtained from PC patients compared to BPH patients [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…As speculated, citric acid was significantly elevated in CRC samples (Amir Hashim et al, 2021 ; Tan et al, 2013 ; Uchiyama et al, 2017 ; Zamani et al, 2014 ). Besides, Buszewska-Forajta et al, found that citric acid was changed in prostate patient and have significant correlations with tumor progression (Buszewska-Forajta et al, 2022 ). In our study, the citric acid concentration was decreased after surgical resection, which is logical with the previous finding.…”
Section: Discussionmentioning
confidence: 99%
“…15 Increased citrate oxidation is frequently observed in malignant cells, resulting in decreased citrate levels in prostatic and seminal fluid in PCa groups. 16 Since citrate can be converted to lactate via the intermediates oxaloacetate and pyruvate, decreased citrate levels could lead to decreased conversion to lactate, which accounts for the observed decreased lactate. Nonetheless, our results that indicate the alteration of lactate in PCa suggests changes in cellular energy metabolism during cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…However, malignant prostatic tissue is unable to accumulate zinc, resulting in increased citrate oxidation and TCA cycle activity 15 . Increased citrate oxidation is frequently observed in malignant cells, resulting in decreased citrate levels in prostatic and seminal fluid in PCa groups 16 . Since citrate can be converted to lactate via the intermediates oxaloacetate and pyruvate, decreased citrate levels could lead to decreased conversion to lactate, which accounts for the observed decreased lactate.…”
Section: Discussionmentioning
confidence: 99%